Infant fecal microbiota composition and attention to emotional faces - Aatsinki Anna K; Kataja Eeva-Leena; Munukka Eveliina; Lahti Leo; Keskitalo Anniina; Korja Riikka; Nolvi Saara; Häikiö Tuomo; Tarro Saija; Karlsson Hasse; Karlsson Linnea (American Psychological Association, 2022)
The gut microbiota has been suggested to influence neurodevelopment in rodents. Preliminary human studies have associated fecal microbiota composition with features of emotional and cognitive development as well as differences in thalamus-amygdala connectivity. Currently, microbiota-gut-brain axis studies cover heterogenous set of infant and child brain developmental phenotypes, while microbiota associations with more fine-grained aspects of brain development remain largely unknown. Here (N = 122, 53% boys), we investigated the associations between infant fecal microbiota composition and infant attention to emotional faces, as bias for faces is strong in infancy and deviations in early processing of emotional facial expressions may influence the trajectories of social-emotional development. The fecal microbiota composition was assessed at 2.5 months of age and analyzed with 16S rRNA gene sequencing. Attention to emotional faces was assessed with an age-appropriate face-distractor paradigm, using neutral, happy, fearful, and scrambled faces and salient distractors, at 8 months of age. We observed an association between a lower abundance of Bifidobacterium and a higher abundance of Clostridium with an increased “fear bias,” that is, attention toward fearful versus happy/neutral faces. This data suggests an association between early microbiota and later fear bias, a well-established infant phenotype of emotionally directed attention. However, the clinical significance or causality of our findings remains to be assessed.